The Effect of G1R1J PSN Education on Improving Knowledge and Preventive Actions Against Dengue Hemorrhagic Fever (DHF) Among Housewives in the Working Area of Wagir Public Health Center - Kitu, Graccelya Angel; AF, Swaidatul Masluhiya; Devi, Hilda Mazarina (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2025)
Dengue Hemorrhagic Fever (DHF) is a major public health problem in tropical countries, including Indonesia. In early 2024, 60,296 DHF cases and 455 deaths were reported nationwide. The high prevalence of DHF is linked to limited knowledge and prevention practices, especially among housewives. This study aimed to examine the effect of Mosquito Nest Eradication (PSN) education using the One House One Mosquito Larvae Monitor (G1R1J) approach in improving knowledge and preventive actions related to DHF. A pre-experimental one-group pre-test and post-test design was used with 79 housewives selected through consecutive sampling. The intervention involved educational materials (leaflets and videos) accessed four times over four weeks. Data were collected using questionnaires and observation sheets and analyzed using the Wilcoxon test. Results showed significant improvements in knowledge (from 55.7% to 97.5%) and preventive actions (from 54.4% to 67.1%) inthe “good” category. The Wilcoxon test indicated a significant effect of PSN G1R1J education on both knowledge (p-value = 0.000 < 0,05) and preventive actions (p-value= 0.001 < 0,05). It is recommended that housewives continue to apply 5M-Plus practices independently. Further studies are suggested to explore other influencing factors such as attitudes, media exposure, and health worker support in DHFprevention.